National anti-corruption system: the paradox between the fight against government corruption and the violation of human rights in Mexico - Vázquez Pérez, Eduardo Daniel (2023)
Corruption has become a systemic problem in Mexico, undermining the foundations of public administration and generating devastating consequences for society at large. The paper addresses the different aspects in which corruption affects the state administration, such as nepotism, bribery and misuse of public resources. These phenomena undermine efficiency and transparency in government management, hindering equitable access to basic services and limiting the country’s development. It also analyzes how corruption affects the human rights of people in Mexico. The lack of integrity and impunity that prevail in corrupt acts generate a climate of injustice and vulnerability for citizens; where corruption undermines equal opportunities, perpetuates socioeconomic inequality and hinders the protection of fundamental rights, such as access to justice, education and health. In conclusion, this article highlights the close relationship between corruption in the administrative sphere of the Mexican State and the violation of human rights. The fight against corruption was essential not only for the consolidation of transparent and efficient government, but also to ensure a fair and equitable society in which all citizens could fully exercise their fundamental rights.